Pengolahan Sampah Rumah Tangga Menjadi Kompos di Kelurahan Tuah Madani Kecamatan Tampan Kota Pekanbaru - Latifa Siswati; Rini Nizar; Anto Ariyanto (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Tuah Madani Subdistrict Tampan District already has a Waste Bank, but to process organic waste into compost, the Garbage Bank cadres in each RW still do not have this knowledge. The Unilak Community Service Team has the required knowledge, and through this activity a transfer of knowledge is carried out, so that the Garbage Bank Cadres will more optimally manage the waste that has been collected in the Waste Banks of each RW. The method of activities that will be given to the community is, awareness, counseling, demonstration, and evaluation. Awareness is intended to give awareness to the Garbage Bank Cadre that managing waste into compost will have a positive impact on the environment. Counseling aims to provide knowledge to the community so that they are more sensitive to their environment, so that the environment will provide results that benefit their families. Demonstration aims to provide knowledge directly, both through picture shows, and direct practice making compost from household waste. And an evaluation is carried out to determine the level of knowledge of partners before and after the activity, and to find out the success of the activity.